Novel behavioral tasks for studying spatial cognition in rats - Klement, D; Blahna, K; Nekovářová, T (Physiological research, 2008)
Spatial tasks in rodents are commonly used to study general mechanisms of cognition. We review two groups of novel spatial tasks for rodents and discuss how they can extend our understanding of mechanisms of spatial cognition. The first group represents spatial tasks in which the subject does not locomote. Locomotion influences neural activity in brain structures important for spatial cognition. The tasks belonging to the first group make it possible to study cognitive processes without the interfering impact of locomotion. The second group represents tasks in which the subject approaches or avoids a moving object. Despite this topic is intensively studied in various animal species, little attention has been paid to it in rodents. Both groups of the tasks are powerful tools for addressing novel questions about rodent cognition.
Keywords: pohybová aktivita; Space Perception; Maze Learning; psychologické testy; kognice; bludiště - učení; prostorové chování; krysa rodu Rattus; Hippocampus; Avoidance Learning; zvířata; hipokampus; učení vyhýbat se; Psychological Tests; Rats; Motor Activity; Animals; Spatial Behavior; Cognition; vnímání prostoru